Community forest management for timber extraction in the Amazon frontier - Medina, G.; Pokorny B.; Campbell, Bruce M. (2009)
Amazonian communities have the potential for improving their livelihoods by efficiently managing their forest resources. However, there is limited understanding of how communities are managing their forests in the dynamic Amazon frontier. This issue was studied in four areas in Bolivia, Brazil and Peru. The most common approach to forest management was found to be informal timber rights negotiations between communities and logging companies. Much less common was community forest management (CFM) for timber extraction supported by NGOs. Case studies revealed that stocks of commercial timber species were depleted by logging companies in only a few years in the logged areas, while CFM initiatives planned rotational cycles but were abandoned when external support ceased. Families received limited financial benefits from both loggers (cash income US$ 1.18/m3 and US$ 28.14/day) and CFM initiatives (cash income US$ 12.57/m3 and US$ 8.69/day). A critical debate on the real potential of these approaches to timber extraction needs to take place.